Treatment of Soft Soil by Sand Columns - Namir K.S. Al-Saoudi; Mohammad M. M. Al-Kaissi; Nawres A. A. Rajab (Engineering and Technology Journal, 2014)
Stone or sand columns are most widely used to improve the engineering properties of soft saturated soils. In principles, sand columns technique is very close to the well-known stone columns technique and the only difference is the backfill materials. The present work focuses on implementing sand columns in soft soil of different diameters, different relative densities considering both floating and end bearing types. The model tests were performed inside a steel container (600mm x 600mm and 500mm in height). Sand columns of diameters ranging between 22mm to 50mm were constructed in beds of soil of undrained shear strength ranging between (15-20) kPa. Each individual sand column was loaded vertically through a rigid circular footing of diameters between 28.6mm to 64.7mm provided an area replacement ratio (as) of (0.6),the ratio of column depth to the column diameter (L/D) was (6). The model test results revealed good improvements of the load carrying capacity of the columns ranging between (1.3 to 1.9) and significant reduction in the settlement over the untreated soil ranging between (0.18 to 0.47). End bearing columns exhibited better results than floating columns and the diameter of column has no effect on bearing capacity as the (as) and (L/D) are constants